2011
DOI: 10.1002/pd.2811
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester fetal nasal bone length in a low‐risk Turkish population

Abstract: The study provides normal ranges of NBL between 16 and 23 weeks of pregnancy in a low-risk Turkish population. Future studies with larger sample sizes including pregnancies carrying high risk for aneuploidy are needed to define cut-off values for NBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…When the 5th, 50th and 95th centile of NBLs were plotted and compared with other ethnic data (Figure ), it was seen that the Indian NBLs were shorter than most other ethnicities. The 5th centile and the median NBLs of the Indian population correlated with the Korean NBLs (Jung et al .…”
Section: Distribution Of Nasal Bone Lengths In Millimetres and The Bpmentioning
confidence: 95%
“…When the 5th, 50th and 95th centile of NBLs were plotted and compared with other ethnic data (Figure ), it was seen that the Indian NBLs were shorter than most other ethnicities. The 5th centile and the median NBLs of the Indian population correlated with the Korean NBLs (Jung et al .…”
Section: Distribution Of Nasal Bone Lengths In Millimetres and The Bpmentioning
confidence: 95%
“…15 Yanik et al have reported nasal bone lengths of Turkish gender as 3.8mm in 16 week old fetuses and 6.35mm in 23 week old fetuses. 16 Many researchers have reported in the literature that nasal bone length increased in parallel with the gestational age. [15][16][17] In present study, nasal bone length was detected as 8.30±2.20mm in male fetuses and as 7.97±1.53mm in female fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many researchers have reported in the literature that nasal bone length increased in parallel with the gestational age. [15][16][17] In present study, nasal bone length was detected as 8.30±2.20mm in male fetuses and as 7.97±1.53mm in female fetuses. The difference between the literature and our study was originated from gestational age difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the impact of [22] , Afro-American [23] , Chinese [11,12] , Korean [13] , Iranian [14] , Turkish [15,16] , Indian [17] , Japanese [18] , South American [19] , and Australian [20] ( table 2 ). How- ever, ethnicity-related variations in NBL during gestation are likely to have an impact on the efficacy of NBL-based screening for trisomy 21.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [11] detected shorter fetal NBs in the Chinese population. Several studies have since shown the impact of race and ethnicity on the nasal bone length (NBL) in second-trimester fetuses: Chinese [11,12] , Korean [13] , Iranian [14] , Turkish [15,16] , Indian [17] , Japanese [18] , Brazilian [19] , and Australian [20] . However, no data have been published about the reference range of NBL of normal fetuses in a large AfroCaribbean population.…”
Section: Introductionmentioning
confidence: 99%